2020
DOI: 10.1136/jech-2019-213313
|View full text |Cite
|
Sign up to set email alerts
|

Cultural participation and all-cause mortality, with possible gender differences: an 8-year follow-up in the HUNT Study, Norway

Abstract: BackgroundCultural activities can promote health and longevity, but longitudinal studies examining a broad spectrum of participation are scarce. This study investigated the gender-specific association between all-causes of mortality and participation in single types of cultural activities, amount and participation frequency.MethodsWe used cohort data from the Nord-Trøndelag Health Study (HUNT Study), Norway (2006–2008), resulting in 35 902 participants, aged 20 and above. Cultural participation in receptive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
3
11
0
1
Order By: Relevance
“… 1 During the following decades, studies examined all-cause mortality as an outcome with prospective designs and starting age ranges similar to ours, where a recent example was an 8-year follow-up study from Norway. 2 The authors followed 35 902 adults from a health survey and reported that non-participation in any receptive activity, except sport events attendance, had an all-cause risk reduction of 21% with two attendances in activities and 31% in three. 2 An English study of an ageing cohort of 6710 community dwelling adults, which started in 2004–2005, revealed that people who attended cultural activities on an infrequent basis (once or twice a year) still had 14% lower mortality compared with those who never attended cultural activities, independent of sex and socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 During the following decades, studies examined all-cause mortality as an outcome with prospective designs and starting age ranges similar to ours, where a recent example was an 8-year follow-up study from Norway. 2 The authors followed 35 902 adults from a health survey and reported that non-participation in any receptive activity, except sport events attendance, had an all-cause risk reduction of 21% with two attendances in activities and 31% in three. 2 An English study of an ageing cohort of 6710 community dwelling adults, which started in 2004–2005, revealed that people who attended cultural activities on an infrequent basis (once or twice a year) still had 14% lower mortality compared with those who never attended cultural activities, independent of sex and socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
“… 2 The authors followed 35 902 adults from a health survey and reported that non-participation in any receptive activity, except sport events attendance, had an all-cause risk reduction of 21% with two attendances in activities and 31% in three. 2 An English study of an ageing cohort of 6710 community dwelling adults, which started in 2004–2005, revealed that people who attended cultural activities on an infrequent basis (once or twice a year) still had 14% lower mortality compared with those who never attended cultural activities, independent of sex and socioeconomic factors. Additionally, those who attended cultural activities more frequently had a considerably (31%) lower risk of dying compared with those who never attended cultural activities.…”
Section: Introductionmentioning
confidence: 99%
“…After they adjusted for several sociodemographic factors, health behaviors, and health and biological risk factors, they found that more non-active social participation was associated with an increased risk of mortality [ 13 ]. The Nord-Trøndelag Health Study (HUNT), a longitudinal study in Norway, reported that the frequency of social participation of less than 1, 1 to less than 2, and 2 or more times per week reduced mortality risk by 18%, 31%, and 39%, respectively [ 14 ]. Participation in both receptive and creative activities at least twice a week was associated with a 29% reduction in cancer-related mortality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 The Nord-Trøndelag Health Study (HUNT), a longitudinal study with a mean follow-up of 8.15 years in Norway, demonstrated that the frequency of social participation of 0.5 to less than 1, 1 to less than 2, and 2 or more times per week significantly reduced the mortality risk by 18%, 31%, and 39%, respectively. 17 Shimatani et al also explored the association between the change of the frequency in social participation and all-cause mortality for individuals aged ≥60 years in Japan; they found that continued or decreased frequency of social participation was associated with a decreased risk of all-cause mortality. Initiation of social participation after the age of 60 years failed to reduce the mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study in Chile, involving individuals aged >60 years, observed that subjects’ participation in social activities had a 22% lower risk of death than those who did not participate during the 5-year study period 16. The Nord-Trøndelag Health Study (HUNT), a longitudinal study with a mean follow-up of 8.15 years in Norway, demonstrated that the frequency of social participation of 0.5 to less than 1, 1 to less than 2, and 2 or more times per week significantly reduced the mortality risk by 18%, 31%, and 39%, respectively 17. Shimatani et al also explored the association between the change of the frequency in social participation and all-cause mortality for individuals aged ≥60 years in Japan; they found that continued or decreased frequency of social participation was associated with a decreased risk of all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%